A Rare Cause of Pediatric Stroke: Left Atrial Myxoma. (March 2017) - Juaneda, Ignacio; Peirone, Alejandro; Contreras, Alejandro; Díaz, Juan; Roca, Federico
We describe a case of sudden-onset left-sided hemiparesis and dysarthria in a five-year-old boy. Acute vascular malformation bleeding or ischemic stroke was suspected. Neurological examination three weeks after the initial event revealed mild residual facial paresis. Brain angiography ruled out a vascular malformation. A work-up echocardiogram revealed a 4-cm left atrial mass compatible with cardiac myxoma. Urgent surgical resection of the mass under cardiopulmonary bypass confirmed the diagnosis. Uneventful recovery followed surgical resection. In this report, we present a partially embolized left atrial myxoma that caused an acute ischemic stroke, which is rarely considered and encountered in the pediatric population.